Improving the quality of sustainability reports through the influence of company size, leverage, company age, media visibility, and profitability - Ahmad Juliana; Ahmad Alfiannur (Faculty of Economics and Business Mulawarman University, 2023)
Companies now convey their social, environmental, and economic performance to stakeholders using sustainability reporting as a key tool. The goal of this study is to examine how factors such as corporate size, leverage, age, media exposure, and profitability affect how much information about sustainability reports is disclosed. The case study for study focuses on businesses that are included in the LQ45 index. Secondary data analysis is used in the quantitative research process. Sustainability reports and financial information that is readily available for a particular period make up the data used. The dependent variable (degree of sustainability report disclosure) and the independent factors (business size, leverage, firm age, media visibility, and profitability) are compared using regression analysis. The results of this study should aid in understanding the variables affecting the degree of sustainability report disclosure among LQ45 index companies. The application of this study suggests that businesses can improve the caliber of their sustainability reports by taking into account the aforementioned factors.